Rethinking Metadata's Value and How It Is Evaluated. Issue 4 (1st October 2020) - Jaffe, Rachel
ABSTRACT: Metadata is becoming more than a tool to facilitate access and retrieval; librarians and other metadata professionals and their users are expecting metadata to perform multiple and diverse purposes and functions: as much as metadata helps connect users to resources, it is expected to appropriately situate resources in relationship to other resources, and within historical and contemporary social contexts. In light of various social justice movements and Diversity, Equity, and Inclusion (DEI) efforts, metadata are being viewed as not only representing resources, but as powerful mechanisms for representing ourselves and others, and moreover, as representative of our organizational, professional, and communal values. Despite these increased demands on metadata and the roles we expect it to play, our frameworks for assessing and evaluating metadata quality have not kept pace. This article proposes that there needs to be increased user-centered research to the end of introducing a new ethical dimension to conventional frameworks and/or expanding our definitions of existing assessment criteria.